Exploring the Effects of Pitch Layout on Learning a New Musical Instrument - Jennifer MacRitchie (Applied Sciences, 2017)
Although isomorphic pitch layouts are proposed to afford various advantages for musicians playing new musical instruments, this paper details the first substantive set of empirical tests on how two fundamental aspects of isomorphic pitch layouts affect motor learning: shear, which makes the pitch axis vertical, and the adjacency (or nonadjacency) of pitches a major second apart. After receiving audio-visual training tasks for a scale and arpeggios, performance accuracies of 24 experienced musicians were assessed in immediate retention tasks (same as the training tasks, but without the audio-visual guidance) and in a transfer task (performance of a previously untrained nursery rhyme). Each participant performed the same tasks with three different pitch layouts and, in total, four different layouts were tested. Results show that, so long as the performance ceiling has not already been reached (due to ease of the task or repeated practice), adjacency strongly improves performance accuracy in the training and retention tasks. They also show that shearing the layout, to make the pitch axis vertical, worsens performance accuracy for the training tasks but, crucially, it strongly improves performance accuracy in the transfer task when the participant needs to perform a new, but related, task. These results can inform the design of pitch layouts in new musical instruments.